Teachers’ Attitudes Towards STEM Education: Exploring the Role of Their Readiness via a Structural Equation Model - Theano Papagiannopoulou; Julie Vaiopoulou (European Journal of Investigation in Health, Psychology and Education)
Over the past decade, there has been an intensified emphasis on STEM education to correspond with the goals of twenty-first century education. Educators play a vital role in executing a cohesive approach to interdisciplinary teaching and learning; hence, considerable focus has been directed towards the elements influencing teachers’ attitudes. The study aimed to provide empirical evidence illustrating the significant influence of teachers’ readiness on predicting attitudes. This was achieved by developing a conceptual model that explores the factors affecting individuals’ attitudes towards teaching STEM courses. The emphasis was put on self-efficacy, commitment, cognitive readiness, emotional readiness, and teaching attitudes. A total of 494 Greek primary and secondary education teachers participated electronically in the survey, answering according to the TRi_STEM and TASET scales. The validity of the conceptual model was evaluated using a structural equation model (SEM). The results demonstrated a positive association among all six factors. More notably, general attitudes towards teaching impact positively, either directly or indirectly, the four readiness variables and, finally, teachers’ attitudes towards STEM education. The current study contributes to the existing body of the literature by identifying and analyzing critical attributes that substantially impact teachers’ attitudes towards teaching STEM courses.